System of analytical indicators for assessing the effectiveness of management decisions in construction and investment activities - MOLODKO, Oleksii (Ways to Improve Construction Efficiency, 2025)
The system of analytical indicators in construction and investment activities serves as a key element in ensuring the validity, adaptability, and effectiveness of managerial decisions. Its purpose is to create a quantitative and qualitative foundation for evaluating the efficiency of management actions in a multifactor environment characterized by high uncertainty and inherent industry risks. These indicators make it possible to measure not only achieved results but also the quality of the decision-making process itself, revealing patterns and interdependencies between project parameters and the level of managerial influence. The analytical indicator system in construction has a cascading structure that encompasses strategic, investment, operational, resource, and risk levels. It is based on the interconnection between indicators of different management tiers, ensuring a “cause-and-effect” logic and enabling the prompt identification of managerial gaps. A distinctive feature of this system is the integration of “hard” quantitative metrics (ROI, budget performance, risk dynamics) with “soft” indicators (employee satisfaction, communication quality, stakeholder trust). To aggregate data, weighted coefficients, fuzzy logic methods, and expert evaluation techniques are applied. Special attention is given to analytical models that allow for measuring the dynamics of decision effectiveness over time, such as the composite management efficiency coefficient, system adaptability indicators, management reactivity measures, and the scenario stability index. Through these models, management gains not only a retrospective evaluation of results but also the ability to forecast future trends. The implementation of an analytical indicator system transforms management from an intuitive process into an analytically grounded one. This enables the digital transformation of managerial processes, the integration of analytics into BIM and ERP environments, and the development of information-diagnostic platforms with data visualization dashboards. Consequently, the analytical indicator system becomes not only a tool for evaluation but also a means of enhancing strategic flexibility, ensuring enterprise resilience, and increasing competitiveness in the construction and investment market.